Hydroxychloroquine (HCQ) Modulates Autophagy and Oxidative DNA Damage Stress in Hepatocellular Carcinoma to Overcome Sorafenib Resistance via TLR9/SOD1/hsa-miR-30a-5p/Beclin-1 Axis - Chen, Ming-Yao (Cancers (Basel), 2021)
SIMPLE SUMMARY: Hepatocellular carcinoma (HCC) is one of the major causes of cancer-associated death worldwide. Development of sorafenib resistance presents a major failure of HCC therapy. We applied a combination therapy approach of hydroxychloroquine (HCQ)–sorafenib, both in vitro and in vivo, with data demonstrating the synergistic effect of HCQ in modulating the expression of toll-like receptor (TLR)-9 and regulating the cancer cells stemness, mesenchymal state, autophagy, and sorafenib resistance through inducing the antioxidant superoxide dismutase (SOD)-1 and apoptosis-allied gene expression and reducing the oxidative DNA damage stress in HCC sorafenib-resistant cells via hsa-miR-30a-5p epigenetic regulation axis. Thus, the combination of HCQ–sorafenib provides a suitable approach in improving therapeutic outcomes of sorafenib-resistant HCC patients. ABSTRACT: Sorafenib is used for treating advanced hepatocellular carcinoma (HCC), but some patients acquire sorafenib resistance. We investigated the mechanisms underlying acquired sorafenib resistance in HCC cells and targeted them to re-sensitize them to sorafenib. In silico analysis indicated that toll-like receptor (TLR)-9 was significantly overexpressed, and that miRNA (hsa-miR-30a-5p) was downregulated in sorafenib-resistant HCC cells, which modulated HCC cell proliferation, oxidative stress, and apoptosis. TLR9 overexpression increased HCC cell proliferation, whereas TLR9 inhibition from hydroxychloroquine (HCQ) decreased HCC cell proliferation, tumor growth, oxidative stress marker (SOD1), and the formation of autophagosome bodies (reduced ATG5 and Beclin-1 expression). Moreover, HCQ treatment reduced epithelial–mesenchymal transition, leading to decreased clonogenicity, migratory ability, and invasiveness. HCQ targeted and reduced the self-renewal capacity phenotype by inhibiting tumorsphere generation. Both in vitro and in vivo results demonstrated the synergistic effect of the HCQ–sorafenib combination on sorafenib-resistant HCC (Huh7-SR) cells, increasing their sensitivity to treatment by modulating TLR9, autophagy (ATG5 and Beclin-1), oxidative stress (SOD1), and apoptosis (c-caspase3) expression and thus overcoming the drug resistance. This study’s findings indicate that TLR9 overexpression occurs in sorafenib-resistant HCC cells and that its downregulation aids HCC suppression. Moreover, HCQ treatment significantly increases sorafenib’s effect on sorafenib-resistant HCC cells.